Importance of Small and Medium Entrepreneurship for The Foreign Economic Relations of Azerbaijan Republic - Ayten A. MEKHRALIYEVA (Communications of International Proceedings, 2022)
Entrepreneurship is one of the most important factors in the formation and development of a market economy, supporting the domestic market. It can solve social problems along with the solution of an important socio-political task - the formation of the middle class, the strengthening of democracy and social institutions, small business. In modern conditions, the intensification of state regulation and the promotion of the development of entrepreneurship, the organizational forms of interaction of government agencies with private entrepreneurship are changing. In this work, there are significant changes in the goals, mechanisms, management apparatus in the combination of state and market regulatory mechanisms, which is necessary to talk about the importance of the analysis of the structure of activities. In order to increase the pace of economic development in Azerbaijan, to apply the improved features of the market economy, the importance of free entrepreneurship, especially innovative entrepreneurship in accordance with the requirements of the time, is very great. Because innovative entrepreneurship allows to increase low production capacity and product quality. The purpose of the study is to study the specifics of the activities of small and medium-sized businesses in Azerbaijan, to identify their origin, principles of operation, their specific features. It is also the subject of research to determine the main directions of export activities of business entities and their impact on foreign economic activity, the volume of import-export operations and trade turnover of the country.
Keywords: Entrepreneurship; Economic Growth; State Mechanisms; Foreign Trade.